Pelatihan Manajemen Usaha Pembibitan Ayam Hibrida Lokal untuk Kader Wirausahawan Unggas di Desa Nusa Kecamatan Lhoknga Kabupaten Aceh Besar - Alkautsar, Alkautsar; Fauhan, Gharsina; Ikbal, M.; Jeksi, Sri; Rahman, Riski Ambia; Salsabila, Nailis; Tridayana, Icha; Zulkifli, Zulkifli; Rahly, Fawwa; Yustendi, Dedhi; Mudatsir, Mudatsir; Makmur, Ali; Mulyadi, Mulyadi; Yaman, M. Aman; Rafika, Rafika (Indo Publishing, 2026)
Increasing the number of young entrepreneurs in the poultry sector is a mandate for universities, given the high market demand for Hybrid Chicken products—a type of chicken that has the potential to produce more and larger eggs. To support the availability of commercial seeds, a 23-day Community Service Programme (PKM) has been implemented, focusing on improving the management capabilities of local hybrid chicken breeding businesses. This programme targeted 12 entrepreneurial cadres (farmer groups and students) through key technical guidance and demonstrations, including artificial insemination and DOC selection. The results showed that the programme was highly successful in transferring knowledge and skills: 90% of participants mastered the material and 85% mastered the technical demonstrations. This success was reinforced by a 100% satisfaction rate among participants, who reported significant benefits. As a follow-up, participants recommended extending the training duration to three months and expanding the scope to other poultry species.